Transições de fase em monocristais de Na2ThF6 - Melo, Wanessa David Canêdo (2008)
In this work we have studied possible phase transitions in Na2ThF6 single crystals using Di erential Scanning Calorimetry (DSC), Raman and Impedance spectroscopies and static simulations. The polarized Raman spectroscopy measurements were performed in the temperature range from 10 K up to 770 K and DSC measurements from 298 K up to 823 K. The results indicate that the Na2ThF6 single crystal are structurally stable in the temperature ranging from 50 K up to 770 K. Below 50 K, a mode with A1 symmetry disappear indicating a possible phase transition. Besides, the bandwidth of the main Raman modes increases with the temperature showing a behavior like Ahrrenius with activation energies of 0,17 eV and 0,16 eV. The Impedance spectroscopy measurements were performed in the temperature range between 298K and 773K in the clivage (311) crystalline plane. The results indicate an increase in the ionic conductivity at high temperatures showing a conduction mechanism with activation energy of 0,28 eV. The imaginary part of the dielectric constant and conductivity present an anomaly at around 735 K, possibly associated to a superionic behavior. The static simulations were performed using the GULP code in the hydrostatic pressure range between room pressure and 20 GPa, showing that the z coordinate of the Na+ ion tends to value 1=2 at around 6 GPa, indicating a possible structural phase transition induced by hydrostatic pressure. The ferroic characteristic of this transition was de ned according to the changes observed for the piezoelectric and compliance tensors.